Planeación operativa de la calidad para el mejoramiento de los servicios turísticos en la Quinta El Rocío del cantón Bolívar - Vera Meza, Andrés Alejandro (2014)
The research aimed to design an operating plan for improving the quality of tourism services offered by the Quinta El Rocío, this study involved a situational analysis, which departed from the delimitation of the study area and determining services offered ; implementation of EFI matrices, EFE, MPC and DAFO helped identify the particular environment (strengths and weaknesses) of the study site; subsequently developed a series of lists (check list) for each of the areas you identify as supply management, storage, equipment and by matrix LEOPOLD control energy, water and waste, based on the characteristics and deficiencies of the place, in each strategies and targets aimed at improving procedures Fifth Rocío this in order to provide better quality products and services are designed. In the final phase a schedule of monitoring and evaluation in the administrative, operational, personnel and infrastructure, which was structured according to the priorities of each area to comply with the proposed theme designed. In conclusion determined to be essential to implement an operational plan on the quality of tourism services Quinta El Rocío as this contributes to the improvement of services, providing a better end product to the consumer.